Investigation of the Relationships among Narcissism, Humanity, Interpersonal Control Perception and Envy in Male and Female Employees - simin Zeqeibighannad; Shahid Chamran; Sahar Hesami (Journal of Educational, Health and Community Psychology, 2020)
Abstract Envy is one of the most common human emotions related directly to interpersonal relationships. The aim of this study was to investigate the relationships among narcissism, common humanity and interpersonal control perception with envy. To do this, 140 male and female employees from Shahid Chamran University of Ahvaz were chosen through random sampling. They completed questionnaires of Hypersensitive Narcissism Scale (HNS), interpersonal control perception subscales of Perceived Control Across Domains Scale (PCADS) and common humanity subscale of Self-Compassion Scale (SCS) and the Envy Assessment based on Islamic Sources. The gathered data were then analyzed by SPSS (21.0 version) and Stepwise Regression Analysis was used to analyze the research hypotheses. The results showed that narcissism and common humanity were the most important predictors of envy in female employees and interpersonal control perception and narcissism were the most important predictors of envy in male employees. These findings have practical implications for management the envy phenomenon in work environment. Keywords: narcissism, common humanity, interpersonal control                 perception, envy